Pagbalangkas: Issues and opportunities on natural heritage sustainability of Samar Island Natural Park (SINP), Philippines - Basis for inclusive organizational management framework - Avi Ben Pestañas Andalecio; Jame Monren T. Mercado; Gezzez Giezi G. Granado; Eric B. Zerrudo (School of Tourism, Universitas Ciputra Surabaya, 2022)
Pagbalangkas is a Filipino term, which means formulation or conceptualization. And in the conceptualization of a place branding strategy, such as the UNESCO World Heritage Site (WHS), stakeholders, specifically the government sector, must understand different factors and aspects of sustainable development. This study explicated the different issues and opportunities for conservation, and sustainable development, specifically for Samar Island Natural Park (SINP), Philippines. Specifically, the study also determines the associations of different efforts mandated and implemented by different government agencies both from the national and local, assessing the impacts and effects of current and potential plans and programs for conserving and sustaining SINP as a future UNESCO WHS and to conceptualized a framework that would highlight the basic factors on place branding development based on the case of SINP. The research used a qualitative-case study design, specifically by measuring information through focus group discussion (FGD) and content analysis on available government-issued documents. Participants from the FGD were representatives from different government agencies from the national, regional, local, and people’s organizations. The gathered information was analyzed through a repertory grid. Based on the research, conceptualizing a place branding development, such as UNESCO WHS, must determine the government organizations, institutions, and systems framework, situation analysis of the place and its community, issues, and opportunities manifested.